Constitutionality in Draft of Omnibus Law in Pancasila Perspective - Lusia Indrastuti (Universitas Slamet Riyadi, 2020)
President Jokowi, in his second leadership, has two major programs. The first is to maintain Pancasila state and to accelerate national development. His second program concerns simplification of domestic regulation that relates with economy through Omnibus Law as a reaction to global economic power shift.The problem is whether the implementation of the Indonesia state legal system can accept Omnibus Law model or not when it is viewed from constitutional perspective or from legislation hierarchy in Indonesia (taking into account constitutional requirements, meaning that it is not contradictive with the 1945 constitution). In the preamble of Omnibus Law draft, article 5 and article 20 the 1945 constitution are mentioned. As formal requirements, both articles provide enough space. It is mentioned in article 5 paragraph 1 that President has the right to propose a law. Furthermore, in article 20 paragraph 2 and 3, it is stated that all bill drafts have to be discussed with House of Representatives, including Omnibus Law. Without mutual consent bill draft cannot be proposed again in the council court in that period. In Indonesia, the technique of legislation drafting is employs the act number 15 year 2019, as the legal basis, that concerns the change over the act number 12 year 2011. Besides that, there is Presidential decree number 87 year 2014 as direct derivative of article 5 paragraph 1, article 20, and article 22 of 1945 constitution. The government does not mention the act number 15 year 2019, act number 12 year 2011 or Presidential decree number 7 year 2014 in the preamble of Omnibus Law proposed. Article 5 and article 20 do not clearly explain the limitation of the kind of act that can be proposed by President. If it is seen through historical aspect of drafting of amendments to the 1945 Constitution, during its session, the People's Consultative Assembly never once discussed the Omnibus Law. Therefore, the spirit of post amendments of article 5 and article 20 the 1945 constitution does not come from the possibility that someday Omnibus Law will be adopted into our acts. The point is drafting bills that is not contradictive with economic and social development goals has to be a priority.